2016
DOI: 10.1161/circimaging.116.004770
|View full text |Cite
|
Sign up to set email alerts
|

Serial Native T1 Mapping to Monitor Cardiac Response to Treatment in Light-Chain Amyloidosis

Abstract: A myloidosis is a condition in which misfolded proteins form insoluble deposits in the extracellular space of various tissues and organs, leading to interstitial expansion and disruption of structure and function. Light-chain (AL) amyloidosis is caused by an underlying plasma cell dyscrasia; cardiac involvement is common, is present in ≈50% of patients at presentation, and is a principal driver of morbidity and mortality.1 In practice, there has been reliance on ECG and echocardiographic features, as well as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“… 22 Serial T1 mapping can therefore be used in amyloidosis to monitor both disease progression and response to therapies. 23 In comparison with AL amyloidosis, TTR amyloidosis usually demonstrates lower native T1 values consistent with lower extracellular volume burden of disease. 24 In this case, elevated native T1 values of 1,450 (3T normal range, 1,100-1,150) and reduced postcontrast T1 of 220 (normal < 440) suggested a moderately high burden of disease, correlating with high uptake on bone scan.…”
Section: Discussionmentioning
confidence: 98%
“… 22 Serial T1 mapping can therefore be used in amyloidosis to monitor both disease progression and response to therapies. 23 In comparison with AL amyloidosis, TTR amyloidosis usually demonstrates lower native T1 values consistent with lower extracellular volume burden of disease. 24 In this case, elevated native T1 values of 1,450 (3T normal range, 1,100-1,150) and reduced postcontrast T1 of 220 (normal < 440) suggested a moderately high burden of disease, correlating with high uptake on bone scan.…”
Section: Discussionmentioning
confidence: 98%
“…In ATTR-CA patients, the recommended follow-up scheme involved 6-month visits with ECG and complete blood tests (including NT-proBNP and troponin) in addition to yearly echocardiography and 24 h Holter monitoring [4]. Some studies have reported the role of CMR in monitoring the treatment outcomes of patients [70,71]. Additional research is required regarding the choice of imaging modalities that are appropriate for tracing therapy-related changes.…”
Section: Role Of Multimodal Imaging In Follow-up and Treatment Monito...mentioning
confidence: 99%
“…While treatments improve the clinical condition of patients with CA, the reduction in native T1 and ECV might represent the amyloid burden abatement, which provides compelling evidence of cardiac amyloid regression. [64][65][66][67] Recent therapeutic developments of CA have been associated with improved outcomes. The evaluation of patient responses would be essential for optimal individualized treatment strategy, closely meshed monitoring is imperative.…”
Section: Parametric Mappingmentioning
confidence: 99%